Who needs extra time? Amniotic membrane wrapped pauci-suture model for rapid anastomoses*. Issue 2 (4th March 2019) - Ercin, Burak Sercan; Bicer, Ahmet; Yigitturk, Gurkan; Cinar, Celal; Cavusoglu, Turker; Uyanikgil, Yigit; Gurler, Tahir
Abstract: An ideal anastomosis method will obtain the highest post-anastomotic vessel patency and will repair the vessel anatomically with minimal thrombosis in an easier, faster and cheaper fashion. To achieve these goals an anastomosis model using an amniotic membrane is introduced. The study was performed on the femoral arteries of 22 Wistar Albino rats (11 control group, 11 experimental group). In the experiment group, the microvascular anastomosis was completed with three sutures and a patch of amniotic membrane which was wrapped around the anastomotic site. The conventional anastomosis technique with eight sutures was performed in the control group. The effects of the model on the patency and histological structure of the vessels were evaluated. As a result, normal patency was determined radiologically and macroscopically in all of the anastomoses. No thrombosis or aneurysm was detected in any of the anastomoses. In the angiographic study, vessel patency was detected in both the control and experimental groups. The average time to complete the arterial anastomosis was 18.14 (±2.84) and 10.39 (±2.45) minutes in the control and the experiment groups respectively. In the histological studies, anti-eNOS staining revealed that endothelin levels were significantly higher in the experimental group. This method describes a new anastomosis model in microvascular surgery with promising results that call for additional experimental studies and further clinical implementations. We believe that this experimental technique can be put into clinical practice as an alternative to the conventional microvascular anastomosis technique.